Pengaruh Return On Asset, Current Ratio, Struktur Aktiva, Dan Pertumbuhan Penjualan Terhadap Struktur Modal - Fitria Ernawati; Roy Budiharjo (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
The purpose of this study was to determine the effect of return on assets, current ratio, asset structure, and sales growth on capital structure. This research uses secondary data in the form of the annual report. This study uses multiple linear regression analysis were for partial testing using the t statistical test and simultaneous testing using the ANOVA statistical test. A statistical test is done by the t-test and multiple linear regression analysis before this test is done first classic assumption test. The result of the research shows that: 1) Based on the partial research result, it can be seen that the amount of return on asset produced by the company has a positive significant effect on debt to equity ratio; 2) The current ratio of the company has a negative significant effect on debt to equity ratio; 3) The assets structure has a positive insignificant effect on debt to equity ratio; 4) The sales growth has a negative insignificant effect on debt to equity ratio; 5) Based on the results of the study simultaneously stated that the variable return on asset, current ratio, asset structure, and sales growth together have a significant influence on the debt to equity ratio.